Resilience Against Workload Pressures and Work Deadlines for State Civil Apparatus in Badung Regency - Ni Luh Sri Wulantari Dewi; Ni Putu Nina Eka Lestari (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
Workload Pressure and Employee Deadlines pose various kinds of challenges and demands from both individual external and individual internal sides. So that individuals experience symptoms of burnout or stress that have an impact on significantly reducing productivity in a company or agency. The onset of burnout or stress symptoms can be minimized or reduced by using appropriate stress coping or regulatory strategies, one strategy that can be used is to use emotion regulation strategies. This study aims to determine the efforts made by ASN Employees at the Regional Secretariat of Badung Regency in surviving the pressure of the deadline workload given and to determine the efforts made by the Regional Secretariat of Badung Regency in order to find out in depth the experience of informants and documentation. The informant determination technique in this study used purposive sampling with a total of 8 informants. Data analysis techniques using the help of NVivo 14 plus software. The results showed that the Regional Secretariat of Badung Regency, especially in the Field of Planning and Finance, some employees experienced symptoms of Burnout Syndrome and Stress due to workload and work deadlines, and needed to be overcome with emotional regulation.